2011
DOI: 10.1007/s11606-011-1743-4
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Manifestations as Indicators of Immune Status in HIV/AIDS

Abstract: A 41-year-old man with human immunodeficiency virus (HIV) infection was admitted with dyspnea on exertion and a nonproductive cough. He was successfully treated for pneumocystis jirovecii pneumonia. Admission physical examination revealed stigmata of four HIV-associated infections demonstrated in the two clinical images: 1) scarring from herpes zoster in the right ophthalmic (V1) distribution of the trigeminal nerve (Panel A, hollow arrow); 2) seborrheic dermatitis in the bilateral nasal folds (Panel A, asteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…In this study, 95.2% of patients had mucocutaneous lesions, among which the most common ones were xerosis, seborrheic dermatitis, HSV infection, and oral candidiasis. These results were in accordance with the studies reported by Levy et al, Foroughi et al, Josephine et al and Noruka et al [ 1 , 8 , 9 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, 95.2% of patients had mucocutaneous lesions, among which the most common ones were xerosis, seborrheic dermatitis, HSV infection, and oral candidiasis. These results were in accordance with the studies reported by Levy et al, Foroughi et al, Josephine et al and Noruka et al [ 1 , 8 , 9 , 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…e present research also found oral candidiasis to be a mucocutaneous disorder with significant association with low CD4 counts, which is consistent with previous studies [8,9,[21][22][23][24]. Furthermore, a statistically significant association was found between furuncle and low CD4 counts, which was compatible with Uthayakumar's research [25].Nevertheless, Ali Azfar et al could not show any association between skin manifestations and CD4 cell counts [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…about 380-450 cells/cumm. 11,20 Among the participants, most dermatologic manifestations were either infectious or noninfectious seen in the second phase of the disease. 21 A study from Nigeria showed that dermatologic manifestations were commonly seen in phases 2 and 3.…”
mentioning
confidence: 99%
“…Levy and Jacobson state, dermatological manifestations among patients with HIV may provide insight into their immune status. 1 Herpes zoster, a common problem, may also be a manifestation of the immune reconstitution inflammatory syndrome (IRIS). 2 According to a study published in 2005, HIV-positive patients were more likely to develop shingles after six months or less of treatment with effective highly active antiretroviral therapy, after restoration of immunity.…”
mentioning
confidence: 99%